Elevating Success: The Impact of a High-Performance Work System and Job Satisfaction on Employee Performance at the Bank - Rosyadi, Rafiq Zainur; Hayati, Keumala; Mardiana, Nova (International Journal of Asian Business and Management, 2023)
Human resources are crucial to a business. Human resources must be managed well to give the company an edge. Companies must consider high-performance work systems and job satisfaction because they affect employee performance. A high-performance work system shows employees that the company cares about their competence, motivation, contribution, and career growth, which improves performance. Job satisfaction is also essential because it improves performance. This causal, quantitative study examines how high-performance work systems and job satisfaction affect PT Bank Lampung Head Office employees' performance. Primary data for this study comes from a Likert scale questionnaire. This study used SPSS 26 to analyze 141 employees using multiple linear regression. Results showed that high-performance work systems significantly improved employee performance. Job satisfaction positively and significantly impacts employee performance, according to the study. This means this study supports the hypothesis. Companies should prioritize high-performance work systems and their implementation to improve employee mobility and promotion, job satisfaction, especially regarding compensation and career expansion, and sick leave rights